Theorizing Style (In Three Sketches). Issue 1 (1st June 2021) - Williams, Nina
Abstract : Style is often saddled to a process of attribution and authorship, where it is deployed to qualify and distinguish between particular genres. Within art and design, these tend to be institutionally coded, such as "Bauhaus" style, or chronologically restricted, as with "Art Deco." In this paper, I sketch out three ways in which style can be theorized as a transformative force, and not simply a referential schema. The three sketches introduce an understanding of style developed in the philosophical writings of Gilles Deleuze and Anne Sauvagnargues and the design practice of the Russian-French Avant Garde artist Sonia Delaunay. Through them, I develop a specific reading of style as a practice rather than as a genre that characterizes a brand or individual. By understanding style as practice, I seek to foreground an expressive capacity of style that is altogether asignifying, impersonal and transversal, as an injunction for rethinking the style of social-scientific research practice.